The Challenge of Teacher Training in the 2030 Agenda Framework Using Geotechnologies - Miguel-Ángel Puertas-Aguilar; Javier Álvarez-Otero; María-Luisa de Lázaro-Torres (Education Sciences, 2021)
Social evolution, globalization, and advances in technology are making it increasingly necessary to offer complete and comprehensive teacher training. This training should produce citizens who are concerned about the planet and its future. These values are embedded in the Sustainable Development Goals (SDGs), the breadth of which allows them to be integrated into the secondary school curriculum for most subjects. To construct a complete teacher training model, the following have been considered: previous studies based on qualitative and quantitative methodologies (the Delphi method and questionnaires for ‘expert’ teachers), the teaching experience of the authors, the action research methodology, and validation by other teachers who use technologies and are concerned about sustainability issues. The result is a teacher training model that is in line with UNESCO’s sustainability competencies and based not only on technology, the scientific content of the subject to be taught, and didactics (pedagogy), but also on education in sustainability and the SDGs that need to be integrated. This approach is expected to produce changes in citizens’ attitudes that contribute to the achievement of the SDGs and lead to the teachers feeling positive about their teaching experiences. However, a systematic application of this approach in classrooms and an assessment of its learning results are still pending.